β1-Blockers Enhance Inotropy of Endogenous Catecholamines in Chronic Heart Failure - Feuerstein, Thomas J.; Schlicker, Eberhard (Frontiers in Cardiovascular Medicine, 2021)
Although β1-blockers impressively reduce mortality in chronic heart failure (CHF), there are concerns about negative inotropic effects and worsening of hemodynamics in acute decompensated heart failure. May receptor theory dispel these concerns and confirm clinical practice to use β1-blockers? In CHF, concentrations of catecholamines at the β1-adrenoceptors usually exceed their dissociation constants (KDs). The homodimeric β1-adrenoceptors have a receptor reserve and display negative cooperativity. We considered the binomial distribution of occupied receptor dimers with respect to the interaction of an exogenous β1-blocker and elevated endogenous agonist concentrations > [KDs], corresponding to an elevated sympathetic tone. Modeling based on binomial distribution suggests that despite the presence of a low concentration of the antagonist, the activation of the dimer receptors is higher than that in its absence. Obviously, the antagonist improves the ratio of the dimer receptors with only single agonist activation compared to the dimer receptors with double activation. This leads to increased positive inotropic effects of endogenous catecholamines due to a β1-blocker. To understand the positive inotropic sequels of β1-blockers in CHF is clinically relevant. This article may help to eliminate the scepticism of clinicians about the use of β1-blockers because of their supposed negative inotropic effect, since on the contrary a positive inotropic effect can be expected for receptor-theoretical reasons.